Current concepts in ACL injuries - Cheatham, S. A.; Johnson, D. L. (The Physician and Sportsmedicine, 2010)
Anterior cruciate ligament (ACL) injuries are common in athletic and physically active populations, and can result in significant functional disability. Female athletes in partichular have been found to be at a relatively high risk for noncontact ACL injuries. Many risk factors, both intrinsic and extrinsic, have been identified. Although some individuals may be treated nonoperatively with an aggressive rehabilitation program, athletes desiring to return to physical activities that require use of the ACL need surgical reconstruction. Surgical techniques remain controversial in regard to tunnel placement and optimal graft choices. Recent literature advocates a more oblique ACL reconstruction to more closely recreate normal knee kinematics and eliminate pathologic rotational laxity. A supervised and intensive rehabilitation program is necessary to achieve desired results. Anatomic and neuromuscular risk factors, often gender related, are the focus of most ACL injury prevention programs.